Branding Digital Pembuatan Konten Dalam Usaha Custom Tumbler Karepmu Project Melalui Platform Tiktok - Aliyah Alfita; Maghfirah Aesthetika (Indonesian Journal of Community Empowerment (IJCE), 2026)
The development of digital technology and social media has brought about significant changes in product marketing and branding strategies, particularly for small and medium-sized businesses. Karepmu Project, a custom tumbler business in Sidoarjo, utilizes the TikTok platform as a digital branding tool to increase product visibility and appeal. This activity aims to implement a creative content creation strategy thru TikTok to strengthen brand image and expand audience reach. The method used is a qualitative approach thru direct practice (action research) in the form of mentoring for creating TikTok video content, including training, observation, and documentation of activities. The results of the activity show an increase in creativity in content creation, publication consistency, and audience engagement, which has a positive impact on the business's digital branding. In conclusion, utilizing TikTok as a digital branding medium has proven effective in building brand identity and enhancing the competitiveness of the Karepmu Project custom tumbler business in the digital era.